2022
DOI: 10.3390/medsci10010014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in Morbidity Markers and Cytological Observations Made in Urine of Schistosoma haematobium-Infected Children: Pre- and Post-Praziquantel Treatment in an Endemic Setting

Abstract: Background: Schistosomiasis is a neglected tropical disease caused by helminths of the genus Schistosoma. Morbidity markers and cytological observations such as squamous metaplastic cells, inflammatory cells, and hyperkeratotic cells in the urine of S. haematobium-infected children may suggest disease severity. They may also help predict severe forms of clinical presentation, such as bladder cancer in later years, among infected ones who miss out on early detection and treatment. Insights into possible changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…They observed several abnormalities, such as squamous cell metaplasia, inflammatory cells, and hyper-keratinosis, which may lead to a severe form of the disease, such as bladder cancer ( 86 ). Later, they showed that Praziquantel intake reduced those abnormalities ( 87 ). None of the studies investigated the host-immune response.…”
Section: Discussion – Controversies Challenges and Roads To...mentioning
confidence: 99%
“…They observed several abnormalities, such as squamous cell metaplasia, inflammatory cells, and hyper-keratinosis, which may lead to a severe form of the disease, such as bladder cancer ( 86 ). Later, they showed that Praziquantel intake reduced those abnormalities ( 87 ). None of the studies investigated the host-immune response.…”
Section: Discussion – Controversies Challenges and Roads To...mentioning
confidence: 99%
“…Pathological changes in the bladder due to SH infection have been reported to include squamous metaplasia of the urinary bladder, keratinizing and non-keratinizing metaplasia, and invasive squamous carcinoma [ 12 ]. In addition, granulocytes, mixed with normal urothelial and squamous cells inflammatory cells, hyperkeratotic cells and squamous metaplastic cells have also been reported [ 13 , 14 ]. The importance of urine cytology in cases of S .…”
Section: Introductionmentioning
confidence: 99%